Epoxy polyurethane nanocomposites filled with fullerite - Rozhnova, R. A.; Galatenko, N. A.; Lukashevich, S. A.; Shyrokov, O. D.; Levenets, Ye. G. (Reports of the National Academy of Sciences of Ukraine, 2015)
New nanocomposite materials based on epoxy polyurethane (EPU) containing nanoscale fullerite in its composition are produced. The influence of small impurities of fullerite on physical and mechanical properties of the nanocomposites is established. The effect of a nanofiller and its concentration on the structure and properties of the composite and the ability to biodegradation in vitro is studied. The developed nanocomposites exhibit the biodegradability, and the presence of nanofillers in the EPU facilitates the course of the process.